Heat transfer enhancement of a heat source located in a wake zone using rectangular vortex generators. (5th August 2016) - Ali, R.K.
Highlights: Heat transfer enhancement of electric device or electronic module near a wake region was investigated. The effect of position, attack angle and size of vortex generator (VG) were presented. NuL of the downstream heat source with VGs can be enhanced by 14.5% within 4676 ⩽  Re L  ⩽ 12, 929. An insignificant increase of 10% in the friction factor with applying VGs was noticed. Abstract: This study investigated experimentally the effect of rectangular winglet vortex generators on thermal performance of square flat heat source near a wake region. Rectangular winglets were fixed on the base board with common inflow orientation to direct the flow toward the core of stagnation zone. The proposed configuration causes significant flow acceleration that enhances heat transfer from near-wake heat source surfaces besides the generated large-scale turbulence vortices. Over Reynolds number range of 4200 ⩽  Re L  ⩽ 12, 300, vortex generators with height ratio ( b / B ) of 3/4–3/2 and length ratio (a/S) of 1/3–2/3 at attack angle of α  = 45° exhibit better thermal performance. Downstream and spanwise distances of x  = (1/3–2/3) S and y  = (2/10–3/10) L have the largest heat transfer enhancement, respectively. The heat transfer was augmented such NuL of the downstream heat source exceeds NuL of single heat source by values reach 9.1% at ReL  = 4676 with applying vortex generator strategy. For physical situation of two rows, NuL of the downstream heat source with installing rectangular winglets vortex generators can be enhanced by 14.5% within 4676 ⩽  ReL  ⩽ 12, 929 at X  =  10/50, Y  =  10/50 and α  = 45°. An insignificant increase in the friction factor of 9.7% over 12, 135 ⩽  Re Dh  ⩽ 34, 305 was noticed.